Adaptive Learning for Early Childhood Education during the COVID-19 Pandemic in Aceh Jaya District: Online vs. Offline - Fitri, Mardi; Abdul Latif, Muhammad (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2021)
Purpose – The issues of teacher facilities and abilities are still a learning obstacle in the pandemic era. Moreover, these issues lead to the non-uniformity of the learning process implementation in early childhood education in Aceh Jaya District. This study analyzes in-depth the reality of the learning process in early childhood education in the pandemic era. Design/methods/approach – This study was conducted using a descriptive qualitative method. The site for the study is in Ceudah Mulia Kindergarten, Teunom District, and Al-Hidayah Kindergarten, Pasie Raya District. Data collection methods were through observation, interviews, and documentation. Analysis of research data was using Miles and Huberman model. The validity tests for the data we are using triangulation of sources and techniques. Findings – The results showed that there was a difference between Ceudah Mulia Kindergarten and Al-Hidayah Kindergarten. Ceudah Mulia Kindergarten conducts online learning via WhatsApp by giving assignments and exciting games with parental guidance. Meanwhile, Al-Hidayah Kindergarten does not use social media platforms or other online learning methods due to various limitations, such as common understanding of technology, the availability of inadequate technology facilities owned by schools and parents of students. Al-Hidayah Kindergarten conducts learning by inviting parents and assigning assignments to students, and the children's work is returned to the school for assessment. However, the role of parents in synergizing with teachers during the learning process of early childhood students in the COVID-19 pandemic has become key. Research implications/limitations – This case study focuses on learning in early childhood education during the pandemic in two early childhood education institutions. The comparison of forms of early childhood learning during the pandemic is illustrated in early childhood education institutions. Practical implications – This case study demonstrated how the application of learning in early childhood education in early childhood education institutions is affected by the COVID-19 pandemic. Originality/value – This paper contributes to knowledge and understanding of learning in early childhood education institutions affected by the COVID-19 pandemic so that stakeholders can formulate policies according to community needs. Paper type Case study